ANALISIA PENENTUAN UMUR PAKAI TANGKI TIMBUN 01-50 TON DI PT.PLN (PERSERO) UIW MALUKU DAN MALUKU UTARA KANTOR PELAYANAN KIANDARAT - Gahsar Rumaday; Leslie. S. Loppies; Nevada J. M. Nanulaitta (Jurusan Teknik Mesin, 2024)
In the oil and gas industry, tanks play a crucial role as storage containers for fluids and fuel oil products, both in the form of volatile, pressurized, and flammable fluids. In addition, tanks are not only found in the oil and gas industry, but also in other sectors such as power plants. In the long period of use, the tank may be damaged due to several factors, including plate depletion caused by cor rosion. This problem can affect the integrity of the tank so that an inspection of the condition of the tank needs to be carried out. The inspection of tank plate thickness and corrosion rate was carried out using the Non-Destructive Examination (NDE) method with the Benetech GM100 Ultrasonic Thickness Gaugge tool. This inspection is urgently needed to determine the remaining life of the tank with reference to the API 653 and API 575 standards. The method used started from literature studies in various references and previous research, after which field data collection was then analyzed in accordance with the findings and applicable provisions. Based on the results of measurements in April 2024, the condition of the 01-50 ton tank is still in good condition, marked by the thickness of course 1-3 is still above the minimum limit that has been determined. For Course 1 Tact is 4.3 mm and Tmin is 0.4064 mm with a corrosion rate of 0.0875 mm/year and a remaining life of 44.49 years. For Course 2 Tact is 4.1 mm and Tmin is 0.2032 mm with a corrosion rate of 0.1125 mm/year and a remaining life of 24.63 years. For Course 3 Tact of 3.9 mm and Tmin of 0.1016 mm with a corrosion rate of 0.1375 mm/year and a remaining life of 28.35 years. It can be concluded that the condition of the 01-50 Ton tank is still in good condition. Keywords: (tank, power plant, plate thickness, corrosion rate, remaining tank life)